THE SIGNIFICANT ROLE OF LINGUA-PSYCHOLOGICAL, PEDAGOGY-DIDACTIC, AND METHODOLOGICAL FACTORS IN THE PLANNING AND IMPLEMENTATION OF SELF-DIRECTED PROGRAMS (Scientific journal of the Fergana State University, 2024)
This study examines the crucial role of lingua-psychological, pedagogy-didactic, and methodological considerations in the effective planning and implementation of self-directed learning (SDL) programs. Through a qualitative approach involving case studies and interviews, we analyze how these factors influence learner outcomes and program success. Our findings highlight the importance of integrating psychological support, pedagogical strategies, and methodological frameworks to foster learner autonomy and enhance educational experiences. We offer insights into optimizing SDL environments for diverse learner populations by addressing the interplay between these considerations. The study underscores the need for comprehensive planning that incorporates these elements to maximize the effectiveness of SDL programs.